A prominence eruption from the Sun to the Parker Solar Probe with multi-spacecraft observations - Niembro, Tatiana; Seaton, Daniel B.; Hess, Phillip; Berghmans, David; Andretta, Vincenzo; Reeves, Katharine K.; Riley, Pete; Stevens, Michael L.; Landini, Federico; Sasso, Clementina; Verbeeck, Cis; Susino, Roberto; et al. (Frontiers in Astronomy and Space Sciences, 2023)
In the early hours of 2021 April 25, the Solar Probe Cup on board Parker~Solar~Probe registered the passage of a solar wind structure characterized by a clear and constant He$^{+2}$/H$^{+}$ density ratio above 6% during three hours. The He$^{+2}$ contribution remained present but faint and intermittent within a twelve-hour window. Solar~Orbiter and Parker~Solar~Probe were in nearly perfect quadrature, allowing for an optimal observing configuration in which the material impacting Parker~Solar~Probe was in the Solar~Orbiter plane of sky and visible off the limb. In this work, we report on the journey of the helium-enriched plasma structure from the Sun to Parker~Solar~Probe by combining multi-spacecraft remote~sensing and in~situ measurements. We identify an erupting prominence as the likely source, behind the Sun relative to the Earth, but visible to multiple instruments on both the Solar-Terrestrial Relations Observatory-A and Solar~Orbiter. The associated CME was also observed by coronagraphs and heliospheric imagers from both spacecraft before reaching Parker~Solar~Probe at 46 R$_{\odot}$, 8 hours after the spacecraft registered a crossing of the heliospheric current sheet. Except for the extraordinary helium enhancement, the CME showed ordinary plasma signatures and a complex magnetic field with an overall strength enhancement. The images from Wide-field Imager for Solar Probe (WISPR) aboard Parker~Solar~Probe show a structure entering the field of view a few hours before the in~situ crossing followed by repetitive transient structures that may be the result of flying through the CME body. We believe this to be the first example of a CME being imaged by WISPR directly before and during being detected in~situ. This study highlights the potential of combining Parker~Solar~Probe in~situ measurements in the inner heliosphere with simultaneous remote-sensing observations in (near) quadrature from other spacecraft.